MRI of sacroiliac joints for the diagnosis of axial SpA: prevalence of inflammatory and structural lesions in nulliparous, early postpartum and late postpartum women. Issue 8 (10th June 2020) - Hoballah, Adel; Lukas, Cédric; Leplat, Christophe; Taourel, Patrice; Pialat, Jean-Baptiste; Sans, Nicolas; Ramos-Pascual, Sonia; Cyteval, Catherine
Abstract : Objectives: To determine the prevalence of bone marrow oedema (BME) at the sacroiliac joint (SIJ) in early postpartum (EPP), nulliparous (NP) and late postpartum (LPP) women, and to identify factors associated with BME presence at the SIJ. Methods: Three groups were obtained: NP (never given birth), EPP (given birth within 12 months) and LPP (given birth more than 24 months). The primary outcome was the presence of BME and/or structural lesions (erosions, osteophytes, ankylosis and sclerosis) at the SIJ MRI. Results: BME prevalence was greater among EPP (33%) than NP (14%, p=0.001), but was not different to LPP (21%, p=0.071). The Assessment of SpondyloArthritis international Society (ASAS) MRI criteria for sacroiliitis were positive in 75%, 71% and 80%, respectively, of EPP, NP and LPP women with BME. EPP (38%) had similar prevalence of sclerosis than LPP (28%, p=0.135), but greater than NP (18%, p=0.001). Lastly, EPP (28%) had similar prevalence of osteophytes than LPP (42%) and NP (27%), although there was a difference between LPP and NP (p=0.006). Conclusions: EPP have higher BME prevalence at the SIJ than NP, EPP tend to have higher BME prevalence compared with LPP and BME presence decreases with time from delivery. Three-quarters of women with BME at the SIJ had a positive ASAS MRI criteria for sacroiliitis, indicating that BME presence as the main criterion for a positive diagnosis can lead to false-positive results. SIJ MRIs should not be interpreted in isolation, since age, time from delivery and other factors may outweigh the pertinence of MRI findings. Trial registration number NCT02956824